2020
DOI: 10.1002/er.6110
|View full text |Cite
|
Sign up to set email alerts
|

Investigation on preparation, thermal, and mechanical properties of carbon fiber decorated with hexagonal boron nitride/silicone rubber composites for battery thermal management

Abstract: Adding thermally conductive filler to polymer matrix is a workable way to increase its thermal conductivity. In this work, carbon fiber (CF) and hexagonal boron nitride (h-BN) were employed to obtain hybrid fillers, firstly, (mh-BN@CF) by electrostatic self-assembly method, then added mh-BN@CF to silicone rubber (SR) matrix to prepare mh-BN@CF/SR composites. There was a good interface compatibility between mh-BN@CF and SR matrix. Besides, the composites can achieve best thermal conductivity when h-BN and CF ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 35 publications
0
9
0
Order By: Relevance
“…The results indicated that the composites with improved thermal conductivity can effectively reduce the battery temperature and highly enhance the performance of the BTMS. [77] In addition, silicone can withstand extreme low or high temperature, delivering excellent thermal stability and showing great potentials in aeronautics and astronautics. [78] Furthermore, silicone can serve as a sealant for multiple energy storage devices, effectively improving the battery performances and reliability.…”
Section: Siloxane For Battery Packsmentioning
confidence: 99%
“…The results indicated that the composites with improved thermal conductivity can effectively reduce the battery temperature and highly enhance the performance of the BTMS. [77] In addition, silicone can withstand extreme low or high temperature, delivering excellent thermal stability and showing great potentials in aeronautics and astronautics. [78] Furthermore, silicone can serve as a sealant for multiple energy storage devices, effectively improving the battery performances and reliability.…”
Section: Siloxane For Battery Packsmentioning
confidence: 99%
“…One paper concluded that 30 wt% of h-BN made the thermal conductivity 3.4 times higher than that of pristine silicone rubber [120]. Another paper showed that the thermal conductivity would be four times higher if using hybrid fillers of h-BN carbon fillers [121]. Apart from conventional systems, there are also studies on using non-conventional systems along with BN.…”
Section: Boron Used In Btmsmentioning
confidence: 99%
“…The mh‐BN@CF/SR composites were used in a liquid‐cooled battery thermal management system (BTMS), exhibiting good mechanical properties, electrical insulation, and thermal stability. The results indicated that the composites with improved thermal conductivity can effectively reduce the battery temperature and highly enhance the performance of the BTMS [77] . In addition, silicone can withstand extreme low or high temperature, delivering excellent thermal stability and showing great potentials in aeronautics and astronautics [78] .…”
Section: Siloxane‐based Molecular Materials For Energy Storage Devicesmentioning
confidence: 99%
“…Reproduced with permission. [77] Copyright 2019, Wiley. rubber (D, R/Si = 2) combined with 3D printing has shown potential towards flexible devices with accurately shaped structures and various patterns.…”
Section: Siloxane As a Substrate For Flexible Supercapacitorsmentioning
confidence: 99%
See 1 more Smart Citation